#TITLE_ALTERNATIVE# - STANY OKTAVIANI (NIM : 10308005); Pembimbing : Dr. Yayan Sugianto, DWI
Galaxy clusters are the largest gravitationally bound structures in the universe. Observations of galaxy clusters is often done to understand the dynamics and evolution of galaxies, as well as the dynamics of the cluster itself. These events correspond to hierarchy of large scale structure formation of the universe, which will form the cluster galaxies and clusters will merge to form larger groups. One of the clusters which experienced merger is cluster Abell 1656. This is confirmed by inspecting its velocity dispersion profile and projected surface density. We obtained the global velocity dispersion of 708.348 km/s for the 1-14 Mpc from the cluster center of Coma. The velocity dispersion value in cluster center is around 800-1100 km/s, which indicates a large difference from the value of the global velocity dispersion. Meanwhile, the projected surface density profile shows a double maximum point. Both of these prove that the cluster Abell 1656 (Coma) is undergoing a merger.